2021
DOI: 10.3390/nano11020364
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Carbon Dots in Optoelectronics

Abstract: Carbon dots (CDs) are an attractive class of nanomaterials due to the ease of their synthesis, biocompatibility, and superior optical properties. The electronic structure of CDs and hence their optical transitions can be controlled and tuned over a wide spectral range via the choice of precursors, adjustment of the synthetic conditions, and post-synthetic treatment. We summarize recent progress in the synthesis of CDs emitting in different colors in terms of morphology and optical properties of the resulting n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 125 publications
(147 reference statements)
1
41
0
1
Order By: Relevance
“…126,127 Due to these features, CQDs have been used in different functional layers of solar cells: electron-transporting layers (ETL), active absorbing layers, hole-transporting layers (HTL), dopants in the active layer, and as an interlayer spacing simply to align and adjust the energy levels of other components. 128 As a result, CQDs-based solar cells are expected to display superior performance. This article reports two recent reviews 119,128 that deal with the role of CQDs in specic types of solar cells.…”
Section: Applications Of Cqds In Solar Cellsmentioning
confidence: 99%
“…126,127 Due to these features, CQDs have been used in different functional layers of solar cells: electron-transporting layers (ETL), active absorbing layers, hole-transporting layers (HTL), dopants in the active layer, and as an interlayer spacing simply to align and adjust the energy levels of other components. 128 As a result, CQDs-based solar cells are expected to display superior performance. This article reports two recent reviews 119,128 that deal with the role of CQDs in specic types of solar cells.…”
Section: Applications Of Cqds In Solar Cellsmentioning
confidence: 99%
“…It has been proven in the literature, theoretically, that the electronic features of carbon-based nanoparticles could be monitored by shape, by morphology, chemical composition and doping. In particular, CDs were considered as nanoparticles with sp 3 -hybridized amorphous carbon cores that contain partially sp 2 -hybridized carbon domains, and it was predicted that the emission of CDs can be red shifted by increase of hybridization factor of those domains within CDs [ 159 ]. Another theoretical investigation showed that covalent-bonded dimers of polyaromatic hydrocarbons at the CDs surface, in contrast to non-interacting monomers, resulted in a red shift and broadening of the PL band, with a decrease in its intensity [ 160 ].…”
Section: Emerging Applications Of Carbon Dotsmentioning
confidence: 99%
“…It has been proven in the literature, theoretically, that the electronic features of carbon-based nanoparticles could be monitored by shape, by morphology, chemical composition and doping. In particular, CDs were considered as nanoparticles with sp 3 -hybridized amorphous carbon cores that contain partially sp 2 -hybridized carbon domains, and it was predicted that the emission of CDs can be redshifted by increase of hybridization factor of those domains within CDs [159]. Another theoretical investigation showed that covalent-bonded dimers of polyaromatic hydrocarbons at the CDs surface, in contrast to non-interacting monomers, resulted in a redshift and broadening of the PL band, with a decrease in its intensity [160].…”
Section: Optronicsmentioning
confidence: 99%